Combating Infectious Disease Importation in Walvis Bay, Namibia: Cross-Border Health Preparedness and Response – A Qualitative Exploration - Jeomba, Mwakondja Alisa; Mahalie, Roswitha; George, Jomin (Disease and Health Research: New Insights Vol. 7, 2024)
Aims: The study aimed at assessing cross-border health measures to combat the importation of infectious diseases between Namibia and its interacting countries. Study Design: An exploratory, descriptive qualitative research design was employed. Place and Duration of Study: The study was conducted at Walvisbay Port Health Services unit between July 2020 and December 2021. Methodology: A total of fifteen (15) key informant interviews (9 female and 6 male age range 20 to 50 years); three (3) focus group discussions (19 female and 9 males; age range 20 to above 50 years) were purposively interviewed until saturation was achieved. In addition, participants’ observation was included in the data collection exercise. Data were thematically analysed with ATLAS.ti version-9 software. Results: A broad range of cross-border health measures are implemented at Walvis Bay. Four main themes namely, cross-border preparedness and response capacities required at entry points; measures to strengthen cross-border health measures; preparedness and response measures in place to combat the importation of diseases, and lastly, adherence to preparedness and response measures emanated from the study. Additionally, the study found that intensified collaborative efforts are required to implement cross-border health measures. Budgetary constraints limit the implementation of border health capacities despite the availability of staff, minimum operational capacities, and legal framework on health measures. Conclusion: Cross-border health measures require a multi-sectoral approach, but obstacles like lack of agreements, operational plans, and joint exercises contribute to infectious disease importation. Additionally, it is crucial to review and update health frameworks, considering the dynamic socio-economic and political contexts. It is essential to engage local communities in developing culturally sensitive health measures to enhance cross-border preparedness and to ensure that entry points are well-equipped for future health crises. Prioritizing border health capacities and collaboration efforts is recommended.